Waste management perspective in Malaysia: a conceptual framework - Mohamad Rosman, Mohamad Rahimi; Fadzil, Faizal Haini; Abdullah, Nurulannisa; Mohd Zawawi, Mohd Zafian; Arshad, Izzatil Husna; Md. Saleh, Mohamad Sayuti; S Baharuddi, Nurfatihah (Academica Press Solutions, 2023)
Waste management is an effort to systematically managing the disposal of household or individual waste. In 2020 scheduled waste in Malaysia increases by 7.5% to a total of 4.0 million tons. Intriguingly, recent statistics also indicated that Malaysia imported 872,531 tons of plastic waste. Besides, the pandemic of Novel Coronavirus 2019 increases the needs for the proper management of waste, especially among the local districts. On the other hand, there is also a scarcity of research on the relationship between website quality characteristic and their impacts on waste management efficiency. As we know, a website is an important medium of communication between the citizens and their local districts. Therefore, the purpose of this study is twofold; first, to identify the current state of waste management among districts in Kelantan, and second, to investigate the impacts of website quality characteristics on the efficiency of waste management among the local district in Kelantan. A quantitative research methodology will be adopted; the instrument will be developed by adopting previous instruments, expert test, pre-tested, pilot tested, before actual data collection. Findings will be analyzed based on a descriptive and inferential relationship using Statistical Package for Social Sciences (SPSS) version 26 and Partial Least Square Structural Equation Modeling (PLS-SEM) using SmartPLS 3.3.3. The findings should contribute as follows (1) indicating the current level of waste management in Kelantan, (2) identifying the current perception of a user towards the waste management services provided by their local authority, (3) identifying the needed waste management services among citizens, and (4) identifying the roles of website quality characteristic on the waste management efficiency.